Interhemispheric Asymmetry of Lateral Sulcus and its Significance in Adult Human Brains: A Cadaveric Study from Southern India - S Valli; S Kanmani Velarasan (International Journal of Anatomy Radiology and Surgery, 2022)
Introduction: Cerebral hemispheres are the two main parts of human brain. Though, the cerebral hemispheres may appear to be identical, one hemisphere is functionally dominant over the other. They also exhibit physical variations. The dominance may be due to lateralisation of cortical functions. In about 90% of the total population, the left hemisphere is dominant over the right where the speech and language areas are located. These areas are situated within the Pars Opercularis (PO) and Pars Triangularis (PT) in the dominant hemisphere of the Lateral Sulcus (Sylvian Fissure). The interhemispheric asymmetry of the Sylvian Fissure (SF) may be the basis of cerebral dominance for language, which is less studied in human beings. These asymmetries are relative and vary according to the functions concerned. Therefore, knowledge of the interhemispheric asymmetries is helpful in neurological diagnosis and management.